PENCEGAHAN STUNTING MELALUI PENYULUHAN GIZI SEIMBANG BERBASIS KEARIFAN LOKAL DI DESA BAN, KARANGASEM, BALI - Komang Triyani Kartinawati; I Made Eka Dwipayana (UNHI Press, 2022)
Ban Village is located in Ban District, Karangasem, Bali which is near the valley of Gunung Agung. Therefore, this village has the potential of fertile soil to produce the nutritious sources of food. Food production from locals is essential to support the daily consumption of people who live in the area. This nutritious food is important for the growth and developmental process of toddlers, especially in their first 1000 days of life. Regarding previous research in 2020, there were 118 cases of stunting, consisting of 77% stunting and 23 % very stunted. This high incidence of stunting is caused by multifactorial, such as family income, inadequate intake of food, and insufficient knowledge about the importance of nutritious food during the first 1000 days of life. Based on that research, the majority of toddlers’ mothers do not aware of the long-term impact of stunting in the future life of their children. They also do not understand that early intervention is beneficial to manage stunting. From the prior situational analysis, it was found that the health education and information were still lacking, therefore people in Ban Village do not know about the definition, the cause, risk factors, signs and symptom and the prevention of stunting. Furthermore, there was lack of health promotion on preventing stunting in the Integrated Health Services (Posyandu). This program is a pilot project to gain awareness and to stimulate community partnership to sustainably hold health promotion and education on preventing stunting in Ban Village, Karangasem, Bali. This program was held on July 9th, 2021 with the participation of community leaders, village midwives, and toddlers’ mothers in Ban Village, Karangasem, Bali. The program was successfully held with good facilities, good communication and interaction with all participants, and enthusiasm of the participants. The content of this program was about the balanced nutrition of weaning food, especially for the first 1000 days of life, and food preparation based on local resources. The health education was given by three respectful speakers in public health with the support of the Community Services Unit in the Faculty of Medicine and Health Sciences, Warmadewa University. The result of this program was an increase of knowledge about balanced nutrition of weaning food, preparation of menu for toddlers, and utilizing local resources for weaning food in toddlers, especially for the first 1000 days of life. Furthermore, there was also enthusiasm in toddlers’ mothers to prepare balanced nutrition in weaning food for their children.